Experimental intraocular infection of Japanese quails (Cortunix coturnix japonica) with genotype VII Newcastle disease virus - Mazlan, Lizma Felisha (2016)
The prevalence of Newcastle disease (ND) in quail industry in Malaysia is not well documented in order to clarify the actual role played by Japanese quails in the epidemiology of ND. Genotype VII Newcastle disease virus (NDV) is the most predominant virus circulating in Malaysia, thus this study was aimed to determine the susceptibility of Japanese quails towards genotype VII NDV. Clinical signs, gross pathological lesions of organs, positive detection of virus in organs and cloacal swabs as well as the expression of the antibody titer were used as parameters to assess the susceptibility of Japanese quails following infection of genotype VII NDV. In this experimental study, 20 quails were divided into three groups (n= 8 for Group A and B; n= 4 for Control Group). The quails in the Group A and B were infected via intraocular route with 0.03 ml of 10 3.5 ELD50 and 10 7.0 ELD50 of NDV strain IBS 002, respectively, while the control group received 1x phosphate-buffered saline (PBS). Depression and ruffled feathers, trachea rales, leg paralysis and torticollis were shown in some of the quails in both infected groups. Based on statistical analysis, there was no significant difference (p > 0.05) in clinical signs between the infected groups. Cloacal swabs that were taken on day seven post-infection for all quails were subjected to one-step reverse transcription real time polymerase chain reaction (RT-qPCR) for detection of virus and the results were found to be negative for all groups. Necropsy was conducted on day seven post-infection and there were no gross pathological lesions of organs observed for quails in both infected groups. Trachea, proventriculus, and caecal tonsil were taken for the detection of NDV by RT- qPCR, and some of the organ samples showed positive detections of virus in both infected groups. Haemagglutination inhibition (HI) assay showed an increase in mean titers of antibody across time and between infected groups but statistical analysis revealed no significant difference (p > 0.05) of antibody reaction across time, but significantly difference (p < 0.05) between infected groups. In summary, Japanese quails are susceptible to genotype VII NDV based on parameters assessed.